(untitled) (Jurnal Teknologi (Sciences & Engineering), 2022)
Sediment transport models in river basins have been developed over the years for various temporal and spatial scales. However, yet few models have been reported for small-scale catchment and still under investigation by many researchers. In this paper, a distributed model based on process was presented for evaluating transportation of sediment in a small catchment scale. The integration of distributed hydrological and sediment model was developed for simulate the soil erosion and sedimentation processes in the catchment area located at Universiti Pertahanan Nasional Malaysia (UPNM). The finding prevailed that the simulation of suspended sediment load over a period of four years gave a good significant result with an average Nash–Sutcliffe Efficiency (NSE) and a Correlation Coefficient (r) were of 0.60 and 0.78, respectively. Moreover, sensitivity analysis revealed that the suspended sediment load in the UPNM catchment was influenced by soil detachability over land (Kf). Overall, the outputs from the present model can be taken as input to predict the soil erosion and sedimentation processes in a small-scale catchment, especially in Malaysia such as in the UPNM.